IP Packet Fragmentation and Reassembly at Intermediate Routers - Pavithra, Gajam; Santosh, D. Teja (International Journal of Computer Sciences and Engineering, 2014)
IP packet fragmentation and reassembly is that, a packet is split into several pieces (fragments) that fit into packet size of the link to be traversed and combine (reassemble) these pieces or fragments at the receiving node to form original packet or datagram. In this paper, we consider reassembly of fragments allowed at the intermediate routers based on the Maximum Transmission Unit (MTU). Without waiting for the destination to reassemble it can be done at the intermediate hops where ever needed. The three fields of IP header used for fragmentation and reassemble are the packet identifier, each fragment is attached with the identifier and reassembling of fragments is done based on the identifier of the fragments. The fragment offset field gives the position of the fragment along with More Fragment (MF bit) and Donï¿½t Fragment (DF bit) flags and the total length field. These two fields fragment offset and fragment length are combinedly used to place the fragments of a packet in right order. This paper, the IP packet fragmentation and reassembly at intermediate routers will be an option to reduce the load on routers due to more number of fragmented packets and improves the performance and increase the efficiency of the router.